Impact of a 6-Month Micronutrient-Dense Plant-Rich Nutrition Intervention on Health and Well-Being at the Worksite. (30th April 2019) - Sutliffe, Jay T.; Gardner, Julia C.; Gorman, Michelle M.; Carnot, Mary Jo; Wetzel, Wendy S.; Fortin, Tricia; Sutliffe, Chloe A.; Adams, Alison
Abstract : This nonrandomized pilot study utilized the health belief model and the theory of planned behavior to assess the effectiveness of perceived behavioral control to determine the impact of a micronutrient-dense plant-rich (mNDPR) dietary intervention on employee health and wellness at the worksite. Seventy-one employees and/or spouses (≥18 years) who met the inclusion criteria were recruited from a regional medical center and a local university. Participants were provided more than 14 hours of in-person lecture combined with take-home materials, and electronic resources to support participants in their transition and adherence to the dietary plan. The study consisted of a 6-hour introductory session followed by weekly 1-hour meetings for 7 consecutive weeks and then monthly 1-hour meetings, for 4 consecutive months over the span of 6 months. Retention of participants was approximately 55 percent. Participants were assessed for measures of weight, waist circumference, and blood pressure; physiological measures of blood cholesterol, triglycerides, blood glucose, and hemoglobin A1c; and well-being measures of gastroesophageal reflux disease, depression, sleep, pain, and worksite productivity, pre-, mid-, and post-intervention. A significant reduction was seen in weight ( F (2, 78) = 19.81, p < 0.001 ) with a mean reduction of 6.65 lb., waist circumference ( F (2, 72) = 40.914, p < 0.001 ) with a mean reduction of 2.8 inches, total cholesterol ( F (2, 70) = 19.09, p < 0.001 ) with a mean reduction of 17.81 mg/dL, HDL ( F (2, 70) = 4.005, p = 0.023 ) with a mean reduction of 3.61 mg/dL, LDL ( F (2, 56) = 10.087, p < 0.001 ) with a mean reduction of 13.1 mg/dL, blood glucose ( F (2, 70) = 6.995, p = 0.002 ) with a mean reduction of 3.7 mg/dL, hemoglobin A1c (paired samples t (39) = 2.689, p = 0.01 ) with a mean reduction of 0.118%, GERD ( F (2, 72) = 7.940, p = 0.001, MSE = 4.225) with a mean reduction of 1.4, depressive symptoms as measured by the PHQ 9 ( F (2, 72) = 10.062, p < 0.001, MSE = 5.174) with a mean reduction of 2.0, and an improvement in sleep quality was seen as measured by the PSQI ( F (2, 74) = 11.047, p < 0.001, MSE = 2.269) with a mean improvement of 1.3. In most cases, improvement occurred across the first two time periods and then leveled off. Blood pressure, triglycerides, pain measurements, and WPAI did not change over time. Effect sizes for significant pairwise comparisons indicated medium to large effects of practical significance. This intervention was therefore effective at improving employee health and well-being. Widespread worksite implementation should be considered to improve the overall wellness of employees.